Features of the classification of types, forms, and structural models of transnational organized criminal groups in the context of the construction and dissemination of mass influence markers on social media platforms - Shalkharov, Е.С.; Nartay, А.Н.; Rysmagambetova, Г.М. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
This article examines the specific features of the classification of transnational organized criminal formations operating within the digital environment and generating markers of mass influence across social media platforms. The study identifies five principal categories of such groups: network-based coordination hubs, hybrid criminal-ideological entities, quasi-legal media platforms, anonymous distributed communities, and temporary mobilization clusters. Three structural types are distinguished, namely centralized, decentralized, and hybrid configurations. In addition, seven functional forms are elaborated, including information injections, viral flash mobs, coordinated harassment campaigns, manipulative narratives, event fabrication, the deployment of bot networks, and the covert promotion of destructive ideas. The primary objective of the research is to develop an integrated criminological classification model of these formations and to assess their impact on societal stability. The study is situated within the broader framework of national security, operational intelligence activity, digital trace monitoring and analysis, threat profiling, and the theory of organized crime. The methodological foundation combines cohort analysis with an examination of the correlation dynamics underlying the dissemination of destructive content. The findings reveal a stable relationship between the activity of these structures and the emergence of interethnic, international, and interreligious conflicts, calls for public disorder, the formation of negative ideologies, the delegitimization of state authority, institutional destabilization, youth radicalization, and the escalation of social tension. The analysis also incorporates elements from a number of historically significant events, including Zhanaozen, Malovodnoye, Chilik, Alisher Navoi-related incidents, Arkankergen, the Zhamyl-Tas episode, Korday, and the January events. The research is oriented toward the development of a predictive and preventive analytical instrument. Its scientific contribution lies in refining the conceptual framework and expanding the typology of organized criminal groups in the digital domain. Its practical value is reflected in the potential application of the proposed classification for threat forecasting, the design of countermeasures, and the enhancement of operational and analytical practices. Additionally, the study identifies several forms of impact, such as the spread of panic sentiments, the erosion of trust in law enforcement institutions, the distortion of historical memory, the intensification of migration-related conflicts, economic destabilization, the growth of cybercrime, the formation of shadow influence networks, and the involvement of minors in unlawful activities. The conclusions provide a more precise understanding of the mechanisms underlying covert control over mass behavior. They may be applied in the development of state-level preventive strategies and interagency coordination frameworks.